A clinical study to evaluate the safe and effective use of a new, single use stethoscope cover to enable reduction in pathogen transmission during auscultation - Nazari-Shafti, Timo Z.; Meyborg, Heike; Iske, Jasper; Schloss, Maximilian; Seeber, Fabian; Friedrich, Aljona; Exarchos, Vasileios; Richter, Anja; Falk, Volkmar; Emmert, Maximilian Y. (Frontiers in Medicine, 2023)
Objectives Stethoscopes carry a significant risk for pathogen transmission. Here, the safe use and performance of a new, non-sterile, single-use stethoscope cover (SC), that is impermeable for pathogens, was investigated by different healthcare professionals (HCPs) in the postoperative care setting of an intensive care unit (ICU). Methods Fifty-four patients underwent routine auscultations with the use of the SC (Stethoglove®, Stethoglove GmbH, Hamburg, Germany). The participating HCPs (n = 34) rated each auscultation with the SC on a 5-point Likert scale. The mean ratings of acoustic quality and the SC handling were defined as primary and secondary performance endpoint. Results 534 auscultations with the SC were performed (average 15.7/user) on the lungs (36.1%), the abdomen (33.2%), the heart (28.8%), or other body-sites (1.9%). No adverse device-effects occurred. The acoustic quality was rated at 4.2 ± 0.7 (mean) with a total of 86.1% of all auscultations being rated at least as 4/5, and with no rating as below 2. The SC handling was rated at 3.7 ± 0.8 (mean) with a total of 96.4% of all auscultations being rated at least 3/5. Conclusion Using a real-world setting, this study demonstrates that the SC can be safely and effectively used as cover for stethoscopes during auscultation. The SC may therefore represent a useful and easy-to-implement tool for preventing stethoscope-mediated infections. Study Registration: EUDAMED no. CIV-21-09-037762.